The mediating role of resilience between caregiver burden and hope among patients with inflammatory bowel disease - Meijing Zhou; Mi Wang; Dan Luo; Caiyun Sun; Qiugui Bian; Jingjing Xu; Zheng Lin (Wiley, 2024)
Abstract Aim To investigate whether resilience mediates the connection between caregiver burden and hope among caregivers of patients with inflammatory bowel disease (IBD). Design A cross‐sectional study. Methods Two hundred patients with IBD were conveniently sampled from two tertiary hospitals in Jiangsu Province, China. The main instruments involved the Zarit Burden Interview, the 10‐item Connor‐Davidson resilience scale, and the Herth Hope Index. We conducted descriptive analysis and Pearson correlations using SPSS 25.0. The PROCESS v3.3 macro analysed the mediating effect. We report the results in line with the STROBE checklist. Results Caregiver burden was significantly negatively connected with hope and resilience, whereas resilience positively correlated with hope. The mediation role of resilience was significant in the relationship between caregiver burden and hope, with mediating effects accounting for 47.86% of the overall effect. Conclusions Resilience partially mediates the association between caregiver burden and hope among patients with IBD. This finding highlights the protective role of resilience in undermining caregiver burden and strengthening hope. Implications for Practice In clinical practice, healthcare providers should perform routine psychological assessments for caregivers of patients with IBD. Furthermore, resilience training should be incorporated into interventions to alleviate caregiver burden and enhance hope. Patient or Public Contribution None.